Prescription in English fire regulation: treatment, cure or placebo?. Issue 2 (20th September 2019) - Law, Angus; Butterworth, Neal
Abstract : This paper presents a discussion of the recent 'ban' on combustible cladding that has been implemented in England following the Grenfell Tower fire. The ban is discussed in terms of its context within the existing regulatory system in England and is analysed in terms of the intended and unintended consequences. Key intended consequences are identified as the prohibition of 'Grenfell-type' cladding, the banning of desktop studies for relevant buildings and the banning of some forms of engineered timber construction. Unintended consequences include the devaluation of private leaseholder's homes, the potential for the problems with the construction industry to be perceived as 'fixed' and a raft of somewhat absurd administrative effects. The authors conclude that the ban has likely been effective in its overall aim but that its success is, ironically, inherently bound up with the efficacy of the very regulations that it was intended to fix. The authors also identify that the new ban is potentially susceptible to 'gaming' by unscrupulous parties within the construction industry.